ENVIRONMENTAL AND SOCIAL IMPACTS OF THE PROGRAMME “INTEGRAL DEVELOPMENT OF THE VARDAR VALLEY” - Arsov, Sasho; Nedanovski, Pece (My University, 2000)
The programme for “Integral development of the Vardar Valley” is a complex and long prepared investment activity, aimed at a more intensive economic utilization of the area alongside the river Vardar and its tributaries. The programme consists of a number of projects which are located in the Vardar Valley and its basin, covering an area of about 80% of the country’s territory. The basic component of the programme is a construction of 16 hydroelectric power plants, whereas it involves many other activities, such as environmental protection of the water resources in the country, provision of drinking and sewerage water, flood protection, development of the tourism and the recreational amenities, river traffic development, land traffic improvement, etc. The paper deals with the most important environmental and social impacts expected to be brought about by the implementation of the programme. Namely, considering the significant interaction with the ecosystems, the implementation of the programme and its further operation will inevitably cause certain negative consequences upon the near environment. In the case of the social impacts, it is necessary to determine the consequences of the people’s resettlement, the destruction of some cultural amenities, etc. caused by the inundation of the land. Disregard for these impacts, and especially the activities necessary to reduce their consequences, might create a serious obstacle to the completion of the individual projects and the programme as a whole within the scheduled time and the planned resources.
Keywords: environmental impact, social impact